Interhemispheric resting-state functional connectivity correlates with spontaneous neural interactions - Hyun Seok Moon; Thanh Tan Vo; Geun Ho Im; Seok-Jun Hong; Seong-Gi Kim (Proceedings of the National Academy of Sciences, 2025)
Functional connectivity (FC), a statistical correlation of pair-wise brain signals from resting-state (RS) functional MRI (fMRI), is a widely used concept for mapping large-scale functional networks in both humans and animals. However, its underlying causal mechanism remains poorly understood, particularly for strong interhemispheric connectivity (e.g., homotopic connections) consistently observed in FC. In this study, we investigated the neural basis of RS FC in mice using fMRI with anatomically defined patterned optogenetic activation and inhibition of excitatory neurons in six cortical regions. Unlike commonly used optogenetic activation, optogenetic silencing suppresses spontaneous neural activity in a localized region, reducing RS synaptic inputs to downstream networked areas. Consequently, fMRI can track spontaneous functional connections without the neural perturbations associated with excitation. While conventional optogenetic activation of excitatory neurons in the targeted cortical areas predominantly elicited their ipsilateral functional responses in both cortical and subcortical regions, optogenetic silencing induced both intra- and interhemispheric cortical responses, which were stronger than cortical-subcortical connections. These effects more closely resembled statistically defined RS FC patterns, providing insight into the underlying mechanisms of intrinsic FC. By modeling synaptic path length-dependent connectivity patterns based on structural connectivity (SC), we found that spontaneous functional connections can be explained by polysynaptic propagation, whereas evoked activity is largely restricted to monosynaptic pathways. These findings highlight the critical role of polysynaptic pathways in shaping spontaneous connectivity, suggesting that RS FC arises from causal interactions of spontaneous ongoing neural activity.